Patterns of physical activity and dietary habit in relation to weight status in adolescent girls - Doustmohammadian, Aazam; Keshavarz, Seyed Ali; Doustmohammadian, Najmeh; Ahmadi, Nayeb Ali (Archives of Advances in Biosciences, 2013)
Healthy eating and physical activity habits formed during childhood can persist into adulthood and prevent or delay premature onset of a number of chronic diseases. The aim of this study was patterns of physical activity and dietary habit in relation to weight status in adolescent girls. In a cross sectional study, using two stage cluster sampling 256 adolescent girls were randomly selected from 8 Semnan secondary schools. Weigh and height were measured and Body Mass Index (BMI) was calculated. In adolescents, anthropometric indices were defined based on the CDC 2000 cut-off points for age and gender-specific BMI. Data of energy and nutrient intake was collected with the 24-hour dietary recall and food record questionnaires. The food frequency questionnaire was used to evaluate daily food consumption. Physical activity was determined using Baecke questionnaire. Data analyzed indicated that daily fat intake (p=0.003, r=+0.18), energy percent of fat (p=0.04, r=+0.01) and fast food frequency (p=0.026, r=+0.139) had significant relationship with BMI percentile. There was a significant relationship between snack frequency and weight status in high school adolescent girls (p=0.023). Data analyzed indicated that physical activity had significant relationship with weight status in adolescent girls (p= 0.0001). The findings suggest that make physical activity enjoyable and improvement food habit among adolescent girls are necessary to induct.